Autoimmunity Methods and Protocols - Perl, Andras; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2004)
Autoimmunity-which affects up to 10% of the world's population-can damage nearly every tissue or cell type of the human body with greatly debilitating or fatal results. In Autoimmunity: Methods and Protocols, expert medical researchers describe in step-by-step detail molecular techniques and in vitro/in vivo model systems for discovering the causes of autoimmunity, as well as how best it may be regulated. The methods to assess the immunological and biochemical pathways relevant for pathogenesis include identifying susceptibility genes, intercellular signaling via cytokines, intracellular signaling through the T-cell receptor, signal processing via protein kinases, identification and enumeration of antigen-specific T cells and autoantibodies, and the dysregulation of apoptosis and its role in modification of self-antigens. Additional protocols serve to establish the presence of and assess inflammatory arthritis, systemic lupus erythematosus, insulin-dependent diabetes mellitus, multiple sclerosis, myocarditis, thyroiditis, scleroderma, uveitis, and vitiligo. These methods can be used to assess the genetic, immunological, and biochemical parameters underlying spontaneous or exogenous antigen-induced diseases. The protocols follow the successful Methods in Molecular Medicine™ series format, each one offering step-by-step laboratory instructions, an introduction outlining the principle behind the technique, lists of the necessary equipment and reagents, and tips on troubleshooting and avoiding known pitfalls. Innovative and easy to follow, Autoimmunity: Methods and Protocols offers today's investigators a cutting-edge collection of readily reproducible methods for establishing and interrogating human and animal models of autoimmune diseases.
Pathogenesis and Spectrum of Autoimmunity -- Pathogenesis and Spectrum of Autoimmunity -- Models of Pathogenesis in Human Autoimmune Disorders -- Mapping the Systemic Lupus Erythematosus Susceptibility Genes -- T-Cell Signaling Abnormalities in Human Systemic Lupus Erythematosus -- TCR ?-Chain Abnormalities in Human Systemic Lupus Erythematosus -- Protein Kinase A and Signal Transduction in T Lymphocytes -- Apoptosis and Mitochondrial Dysfunction in Lymphocytes of Patients With Systemic Lupus Erythematosus -- Methods for Inducing Apoptosis -- Measurement of Cytokines in Autoimmune Disease -- Evaluation of Autoimmunity to Transaldolase in Multiple Sclerosis -- Animal Models of Autoimmunity -- Animal Models for Autoimmune Myocarditis and Autoimmune Thyroiditis -- Animal Models of Insulin-Dependent Diabetes -- Generation, Maintenance, and Adoptive Transfer of Diabetogenic T-Cell Lines/Clones From the Nonobese Diabetic Mouse -- Experimental Use of Murine Lupus Models -- The Anti-DNA Knock-In Model of Systemic Autoimmunity Induced by the Chronic Graft-vs-Host Reaction -- Murine Models of Lupus Induced by Hypomethylated T Cells -- The Mouse Model of Collagen-Induced Arthritis -- Proteoglycan Aggrecan-Induced Arthritis -- Mouse Models of Multiple Sclerosis -- Experimental Autoimmune Encephalomyelitis -- Animal Models of Scleroderma -- Rodent Models of Experimental Autoimmune Uveitis -- Autoimmune Depigmentation Following Sensitization to Melanoma Antigens.
Keywords: Immunology; Immunology